2022
DOI: 10.18632/aging.204237
|View full text |Cite
|
Sign up to set email alerts
|

Bridging cognition and action: executive functioning mediates the relationship between white matter fiber density and complex motor abilities in older adults

Abstract: Aging may be associated with motor decline that is attributed to deteriorating white matter microstructure of the corpus callosum (CC), among other brain-related factors. Similar to motor functioning, executive functioning (EF) typically declines during aging, with age-associated changes in EF likewise being linked to altered white matter connectivity in the CC. Given that both motor and executive functions rely on white matter connectivity via the CC, and that bimanual control is thought to rely on EF, the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Tessitore et al (2012) reported that severity of freezing of gait was associated with a reduction of functional connectivity within the two cortical networks: executiveattention (PFC) and visual (right occipito-temporal gyrus) networks [36]. In addition, executive function, which is mainly supported by the dlPFC, is positively associated with hand dexterity [37][38][39]. These findings suggest that the target brain areas for PD treatment should include not only the cortico-basal ganglia motor circuits, but also cortical circuits such as the dlPFC.…”
Section: Effects Of Tdcs Over the M1 Dorsolateral Pfc (Dlpfc) And Cer...mentioning
confidence: 99%
“…Tessitore et al (2012) reported that severity of freezing of gait was associated with a reduction of functional connectivity within the two cortical networks: executiveattention (PFC) and visual (right occipito-temporal gyrus) networks [36]. In addition, executive function, which is mainly supported by the dlPFC, is positively associated with hand dexterity [37][38][39]. These findings suggest that the target brain areas for PD treatment should include not only the cortico-basal ganglia motor circuits, but also cortical circuits such as the dlPFC.…”
Section: Effects Of Tdcs Over the M1 Dorsolateral Pfc (Dlpfc) And Cer...mentioning
confidence: 99%
“…In particular, improving cognitive functions (attention, inhibition, visuospatial capacities, etc.) is important because they strongly determine behavioral adaptability in everyday life situations and complex movement tasks [ 2 , 3 , 4 , 5 ]. It is widely accepted that both endurance and muscular resistance training, when performed separately or in association, effectively counteract the effects of aging on cognitive capacities [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many deleterious effects of aging, deterioration of manual dexterity is one that can lead to difficulty in performing instrumental activities of daily living, such as writing, cooking, gardening, working on crafts, and opening a bottle [ 1 3 ]. These principal aging-associated changes are observed in both men and women, especially those older than 65 years [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manual dexterity is related to not only executive function but also muscle strength [ 2 , 9 ]. Moreover, the performance of executive functions is related to the motor control performance (i.e., manual dexterity) of both hands, especially the non-dominant hand in older adults [ 3 , 10 , 11 ]. Manual dexterity is particularly important to ensure independent living of older adults owing to its association with the performance of instrumental activities of daily living [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation